2020
DOI: 10.3390/microorganisms8070995
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Microbial Signatures Predictive of Prebiotic Action of Neoagarotetraose in a Dextran Sulfate Sodium-Induced Murine Colitis Model

Abstract: Neoagarotetraose (NT), a hydrolytic product of agar by β-agarase, is known to possess bioactive properties. However, the mechanisms via which NT alleviates intestinal inflammation remain unknown. In this study, a dextran sulfate sodium (DSS)-induced murine model was developed to evaluate the effect of NT on gut microbiome and microbial metabolism using 16S rRNA gene sequencing and untargeted metabolomics. Our data demonstrate that NT ingestion improved gut integrity and inflammation scores. NT reversed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…There is growing evidence of roles of intestinal metabolites as biomarkers of human diseases such as colorectal cancer, 28 colitis, 29 irritable bowel syndrome, 30 and Parkinson’s disease. 31 In this study, N-Palmitoylsphingosine, Methylguanidine and Erucamide were found to have satisfactory discriminative power to distinguish the KT-AMR and ESRD groups.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence of roles of intestinal metabolites as biomarkers of human diseases such as colorectal cancer, 28 colitis, 29 irritable bowel syndrome, 30 and Parkinson’s disease. 31 In this study, N-Palmitoylsphingosine, Methylguanidine and Erucamide were found to have satisfactory discriminative power to distinguish the KT-AMR and ESRD groups.…”
Section: Discussionmentioning
confidence: 99%
“…N,N-dimethylalanine is another pigeon pea metabolite that has not been extensively characterized, but this compound had been previously investigated to characterize the mechanism in which neoagarotetraose alleviates intestinal inflammation. The N,N-dimethylalanine pathway was suggested to play a role in the prebiotic actions of neoagarotetraose ( Liu et al, 2020 ). We put forth that pigeon pea derived metabolites in the diet do merit evaluation for actions in the human gut.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested the signatures of micriobial composition and metabolites might be used to predict the action mechanisms of prebiotic or probiotic. 24,[35][36][37][38] The presenting results suggested that FOS supplementation might prevent the DSS-induced dysbiosis of gut microbiota, by increasing the abundance of potentially beneficial bacteria (e.g., Faecalibaculum and Bifidobacterium) and decreasing the abundance of potentially harmful bacteria (e.g., Mucispirillum), but the mechanisms need to be further explored.…”
Section: The Modulation Of Gut Microbiota By Fos Supplementation In Acute Colitis Micementioning
confidence: 95%